ANALYSIS OF COMPLIANCE WITH SHARIA PRINCIPLES OF MURABAHAH FINANCING AGREEMENTS AT PT. BPRS RAHMAH HIJRAH AGUNG LHOKSEUMAWE CITY - Haris Al Amin; Abdul Halim; Syawal Harianto; Aisara Rizkya; Abi Waqqash (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The purpose of this study is to analyze the practice of applying sharia principles to murabahah financing contracts at PT. BPRS Rahmah Hijrah Agung Lhokseumawe City and analyzing sharia principles of murabaha financing agreements at PT. BPRS Rahmah Hijrah Agung City of Lhokseumawe has complied or not complied with PSAK No. 102. The results of the study conclude that murabahah financing at the Rahmah Hijrah Agung BPRS, Lhokseumawe City, is in accordance with PSAK 102, namely murabahah payments can be made in cash or in deferred. Deferred payments are payments made not when the goods are delivered to the buyer, but payments made in installments or all at once at a certain time. The recognition and measurement of murabahah financing at BPRS Rahmah Hijrah Agung Lhokseumawe City is in accordance with PSAK 102, except when there are arrangements in installments and receipt of installments in arrangements on margin, BPRS Rahmah Hijrah Agung does not recognize anything. However, if in the following month the customer pays arrears, BPRS Rahmah Hijrah Agung records it according to the monthly installments that have been set at the beginning. Presentation of Murabahah at BPRS Rahmah Hijrah Agung Kota Lhokseumaw is in accordance with PSAK 102 because it has presented receivables, deferred murabahah margins, and deferred murabahah expenses in accordance with those in PSAK 102. Disclosure of Murabahah financing is in accordance with PSAK 102 because BPRS Rahmah Hijrah Agung Kota Lhokseumawe has disclosed anything that needs to be disclosed at the time of the transaction in accordance with PSAK 102.